Back to the clinic: without a rationale there is no worthy research question - Talavera, Juan O. (Gac Med Mex, 2019)
A clinical research question requires the concurrence of clinical experience and knowledge on methodology and statistics in that who formulates it. Initially, a research question should have a structure that clearly establishes what is that which is being sought (consequence or outcome), in whom (baseline status), and by action of what (maneuver). Subsequently, its reasoning must explore four aspects: feasibility and reasonableness of the questioning, lack of a prior answer, relevance of the answer to be obtained, and applicability. Once these aspects are satisfactorily covered, the question can be regarded as being “clinically relevant”, which is different from being statistically significant, which refers to the probability of the result being driven by chance, which does not reflect the relevance of the question or the outcome. One should never forget that every maneuver entails adverse events that, when serious, discredit good results. It is imperative to have the possible answer estimated from within the structure of the question. The function of clinical research is to corroborare or reject a hypothesis, rather than to empirically test to find out what the outcome is.